Critical stasis and disruptive performances: ICJ and the Anwar R trial in Koblenz - Koleva, Petya Mitkova (Theoretical criminology, 2021)
This article explores the extraterritorial criminal court case against Anwar R, a high-ranking member of the Syrian regime on trial for crimes against humanity in Koblenz, Germany. Empirically anchored in ethnographic fieldwork conducted in Koblenz and with the Commission for International Justice and Accountability, the article illuminates the trial as a ‘disruptive performance’. The case against Anwar R punctuates two instances of negative stasis and unsettles two accounts of chronicity, namely, those of the Syrian conflict and of the field of international criminal justice. In order to illuminate the trial as a disruptive performance, the article empirically situates the Koblenz case both in relation to the Syrian war that it relates to, to the international criminal justice apparatus that it is a part of and to the underlying compilation of evidence that substantiates it. It thus clarifies both the symbolic potential and the constitutive process that has brought it into being.